2007
DOI: 10.1002/biot.200600230
|View full text |Cite
|
Sign up to set email alerts
|

Process development for the production of prebiotic galacto‐oligosaccharides from lactose using β‐galactosidase fromLactobacillussp.

Abstract: Galacto-oligosaccharides (GOS) are formed from lactose in discontinuous mode of conversion using beta-galactosidase from Lactobacillus sp. (beta-gal). The discontinuous process was optimized for technical application with regard to GOS yield, enzyme preparation, reaction temperature and substrate source. It proved to be advantageous to directly apply the crude cell-free enzyme extract for the conversion, since similar GOS yields and composition were obtained as when using the pure enzyme preparation, but expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…Based on the detailed analysis of the carbohydrate mixture profile, the permeabilized cells of P. anthophila strains display a high preference for the formation of galactosyl β(1 → 6) and β(1 → 3) linkages. This result was similar to that obtained with β-galactosidases from LAB [30][31][32]39].…”
Section: Kinetics and Gos Production Profile With Permeabilized Cellssupporting
confidence: 89%
“…Based on the detailed analysis of the carbohydrate mixture profile, the permeabilized cells of P. anthophila strains display a high preference for the formation of galactosyl β(1 → 6) and β(1 → 3) linkages. This result was similar to that obtained with β-galactosidases from LAB [30][31][32]39].…”
Section: Kinetics and Gos Production Profile With Permeabilized Cellssupporting
confidence: 89%
“…It was reported that there is no obvious difference in the obtained GOS yields using either pure or crude β-galactosidase at 37°C (Splechtna et al 2007). Because of the GRAS status of S. thermophilus it is also safe to use the crude extract in food and feed applications.…”
Section: Discussionmentioning
confidence: 98%
“…Data gleaned from the literature showed that maximum GOS yield is largely influenced by initial lactose concentration (Cho et al 2003;Splechtna et al 2007;Valero 2009). This dependence on initial lactose concentration has at least two contributing factors: increased availability of saccharide galactosyl acceptors, and decreased availability of water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations